Pengaruh Perendaman Plat Gtsl Resin Akrilik Heat Cured pada Pasta Gigi Dengan dan Tanpa Ekstrak Ethanol Daun Sirsak (Annona Muricata L.) Konsentrasi 35% Terhadap Pertumbuhan Candida Albicans (Kajian In Vitro) - 'Amalia, Fitri; , drg. Soetomo Nawawi, DPH.Dent,Sp.Perio (K); , drg. Nilasary Rochmanita S, MDSc (2015)
Background: Dental artificial acrylic resin always contacted with saliva, drinks, and foods, so that it becomes a stain formation, tartar and plaque. Candida albicans which is the part of normal flora of the oral cavity can penetrate the acrylic resin and grows on the surface of the denture that can infect the soft tissues. Denture cleaning can be done mechanically using brush and toothpaste. Toothpaste contain triclosan, which serves as antiplaque material. However, the addition of triclosan to inhibit the effect of Canida albicans's growth is not good, which is caused the toxicity. The function of soursop leaves is to treat various of diseases and it has an antibacterial and antifungal effects which contains flavonoids and tannins that can inhibit the growth of Candida albicans. The effective concentration that inhibits Candida albicans in the acrylic resin heat cured plate is 35%. Methods: This study used pure laboratory experimental research. The sampling method was calculated with the Federer's formula. The samples were acrylic resin heat cured plate. The growth's effect of Candida albicans in the acrylic resin heat cured plate was analyzed using Independent test t-test with 95% significance level. Results: From the analysis, the data shows that there was a significant growth of Candida albicans, p = 0.000 (p <0.05). Conclusion: Toothpaste with additional ethanol extract of 35% soursop leaves (Annona muricata L.) concentration inhibited the growth of Candida albicans in the resin acrylic heat cured plate compared with toothpaste without additional ethanol extract of 35% soursop leaves (Annona muricata L.) concentration